2004
DOI: 10.1016/j.ejop.2003.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular data and the evolutionary history of dinoflagellates

Abstract: New sequences of ribosomal and protein genes were combined with available morphological and paleontological data to produce a phylogenetic framework for dinoflagellates. The evolutionary history of some of the major morphological features of the group was then investigated in the light of that framework. Phylogenetic trees of dinoflagellates based on the small subunit ribosomal RNA gene (SSU) are generally poorly resolved but include many wellsupported clades, and while combined analyses of SSU and LSU (large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
227
4
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(252 citation statements)
references
References 128 publications
17
227
4
4
Order By: Relevance
“…The branching order of these groups is highly congruent with recent classification of the alveolates (Cavalier-Smith, 2004), but whether the MA should be included among the dinoflagellates or as sisters to them is still unclear (see Massana et al, 2008). This unresolved branching order between the dinoflagellates and the MA (Figure 1) could be due to a rapid radiation, early in the evolution of dinoflagellates (Saldarriaga et al, 2004;ShalchianTabrizi et al, 2006); multiple gene phylogenies are needed to help determine the relationships between these groups. The apicomplexans were retrieved as monophyletic (75%, 0.98 pp), whereas Colpodella sp.…”
Section: Resultssupporting
confidence: 62%
“…The branching order of these groups is highly congruent with recent classification of the alveolates (Cavalier-Smith, 2004), but whether the MA should be included among the dinoflagellates or as sisters to them is still unclear (see Massana et al, 2008). This unresolved branching order between the dinoflagellates and the MA (Figure 1) could be due to a rapid radiation, early in the evolution of dinoflagellates (Saldarriaga et al, 2004;ShalchianTabrizi et al, 2006); multiple gene phylogenies are needed to help determine the relationships between these groups. The apicomplexans were retrieved as monophyletic (75%, 0.98 pp), whereas Colpodella sp.…”
Section: Resultssupporting
confidence: 62%
“…Early position of Noctilucales and athecate paraphyly. Athecate dinoflagellates have long confounded dinoflagellate molecular phylogenies as a result of their intermixing with thecate taxa, for example within the so-called Gymnodiniales-Peridiniales-Prorocentrales (GPP) complex (21), or as a result of the unstable position of certain outliers like the Noctilucales, which have at times been placed as basal or nested deeply inside the group (12,16,22). Our analyses resolve these issues and help reconcile dinoflagellate morphological and molecular data in several important ways.…”
Section: Resultsmentioning
confidence: 77%
“…Dinoflagellates have left a fossil record that is one of the richest among protists, and many preserve a detailed record of tabulation through reflection of thecal plates that provide insights into the history of some modern taxa, as well as extinct groups. They have also left an extensive biogeochemical record (i.e., sterols), but reconciling this evidence with poorly resolved gene phylogenies has been difficult (15,16).…”
Section: Significancementioning
confidence: 99%
“…It has been suggested that this species is a misnamed member of the peridinialean genus Amphidiniopsis, which is a heterotrophic sanddwelling genus with diverse cell morphologies and tabulation (Table 1; Hoppenrath et al, 2004;Saldarriaga et al, 2004). The type species of Amphidiniopsis, A. kofoidii, shares features with Archaeperidinium minutum, H. litoralis and T. dragescoi, viz.…”
Section: Molecular Phylogenetic Inferencesmentioning
confidence: 99%